PENINGKATAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA MISSION FRUITS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR - Ainamita Zunnurain; Anni Malihatul Hawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the Student Team Achievement Division (STAD) model assisted by Mission Fruits media on elementary school students' conceptual understanding. The issue addressed is the low level of students' conceptual understanding during the learning process. This research uses a quantitative approach, with the population consisting of all students at SDN Susukan 01, and the sample includes students from classes IIIA and IIIB at SDN Susukan 01. Data analysis was conducted using normality tests, homogeneity tests, independent sample t-tests, regression tests, and paired sample t-tests. The results of the study show: (1) There is a significant difference between the experimental class, which used the Student Team Achievement Division (STAD) model assisted by Mission Fruits media, and the control class, which used the Student Team Achievement Division (STAD) model without the media. This is evidenced by a significance value of 0.002 < 0.05 based on the independent t-test. (2) The Student Team Achievement Division (STAD) model assisted by Mission Fruits media significantly influences students' conceptual understanding, as indicated by a significance value of 0.000 < 0.05 based on the regression test. (3) The Student Team Achievement Division (STAD) learning model assisted by Mission Fruits media is effective in improving students' conceptual understanding. This is shown by the comparison between the post-test and pre-test results in the experimental class, which indicates that students' conceptual understanding in the post-test is higher than in the pre-test. The significance value obtained in the paired sample test is 0.000 < 0.05. The conclusion of this study is that the Student Team Achievement Division (STAD) learning model assisted by Mission Fruits media is effective in enhancing students' conceptual understanding. Keywords:Student Team Achievement Division (STAD);Conceptual Understanding; Mission Fruits